Desarrollo de un simulador de circuitos R-C-L de corriente alterna mediante el software LabVIEW, - Jaya Armijos, Manuel Hernán (2015)
The present technical report serves to reinforce the theoretical knowledge studied in class about Ohm's Law, the different types of electric circuits, etc. In each process conducted will be observed comparing the theoretical data arising from calculations on paper, and experimental data performed with the LabVIEW software. Before working draft RCL circuits alternating current through the LabVIEW software, should begin by the foundation, which is to understand the basics of voltage, electric current, electric resistance, etc. It is elementary to differentiate between connections in series, parallel and mixed. The processes are explained step by step, answering each of the questions of the ten guidelines drawn work so that everything that has been done in practice is analyzed, and a theoretical foundation and mathematical analysis of each calculation is presented . It will be seen that the theoretical and experimental data are closely related and that both theory and practice are of great importance in the study of this subject. For the use of LabVIEW great programming experience is required as icons, terms and ideas familiar to students of this area are used, and relies on graphical symbols instead of written language to build applications, it is for this reason we have seen fit to use this software for the development of this project.